LANGUAGE CHOICE PERFORMED BY JAVANESE CHILDREN AND TEENAGERS AT KALASAN SUBDISTRICT, YOGYAKARTA INDONESIA - Agus Wijayanto (Kajian Linguistik dan Sastra, 2007)
Javanese language is geographically spoken in wide areas; however, it seemsthat its speakers began to give up using it. This can be seen that the quality of itsusage among the young Javanese is deteriorated. This phenomenon mainly happensin the urban areas where the young Javanese tend to use Indonesian languagerather than Javanese language. They think that Javanese language is complicatedrequiring its speakers some regulations and etiquettes, thus they tend to use Indonesianlanguage that is considered as neutral and easy. If this language attitudeoccurs for a long period of time, the Javanese language will be abandoned by itsspeakers or die. The research sample is taken by restricted random sampling technique.They are 244 children and teenagers (between 5 to15 year old ) living insome housings in Kalasan regency. They are chosen from the genuine Javanesefamily whose parents and grand parents are Javanese in nature. The research datais all information about language choice of Javanese and Indonesian languagedone by the subjects of the study in the domain of their houses, schools, and publicplaces spoken to parents, teachers, schoolmates, friends at home, neighbors, auntsand uncles, guest or visitors, grand-mothers and fathers, and strangers. The datais taken by survey questionnaire. Based on the field data, most of the subjectschoose Indonesian language when they communicate with parents, teachers, schoolmates,friends at home, neighbors, aunts and uncles, guest or visitors, grand-mothersand fathers, and strangers. Most of them speak in Low level Javanese (ngoko) toparents, schoolmates, friends at home, neighbors, aunts and uncles, grand-mothersand fathers. They rarely use Middle level Javanese (madya) and High level Javanese(krama).